Normativity of Prescriptions in Adolf Reinach’s Aprioristic Theory of Right - Gołębiewska, Maria (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
In the Logical Investigations, Edmund Husserl defines that which is normative as the objectively regular with its rules of regularity, which can be recognised rationally – normativity concerns the being itself and the rational cognition of the being (logic as a normative discipline establishing the rules of scientific knowledge, as the science of science). Instead, Adolf Reinach in The Apriori Foundations of the Civil Law defines the notion of norm as polysemantic and distinguishes the legal provisions (the prescriptive sentences), formulated within a given community, from the basic norms which are grounded in the objective (including moral) justness of the states of affairs. The obligation of the being and the obligation of acting exist in themselves, independently from cognition. In turn, “enactments and the propositions which express enactments” as a kind of normative sentences have the character of normalisation, but they require a person to pronounce them. The prescriptions realise and refer to what is objectively being and to the objectivity of what is being and obligatory. In my text, I present Reinach’s position on the relations between norms and provisions (as prescriptive propositions “which express enactments”) referring his theories to the Husserlian concept of normativity.